Green Marketing: A Study on How Industries Transform into Green Business Industries - Gunwani, R; Chhabra, I; Rathore, D (International Journal of Computer Sciences and Engineering, 2025)
Green Marketing is the concept in which manufacturer markets the products that is presumed to be environmentally safe. In recent years the term green or eco marketing have reflect a growing concern at all the levels and shows its impact on increased consumptions on physical environment. Environmental benefit and sustainability are the two important characteristics of green business. Now –a-days both manufactures and customers understood the importance of environment and the reason for the deterioration of the environment. Purpose: The purpose of this study is to investigate issues that determine the long term efficiency of green marketing. A number of companies are starting to explore environmental policies based on products rather than process. The desire to protect the environment and to maintain its sustainability significant efforts should be made to make environment green. Design and Methodology: This research paper is based on secondary data collected through several literature studies. The recent achievements within each of these research streams are briefly reviewed. Implication: The solutions that green marketing concept provide for the problems, that environment face is that – Judicious use of resources, waste management. These solutions are adopted by the companies to promote their product in the market. So it has been conclude that the concept of Green Marketing has become the need for the today’s manufactures for their survival in today’s competitive world and to achieve their ultimate target that is “Profit”.